Tradisi Besahian: Budaya, Religiositas dan Modernisasi dalam Sistem Pertanian Masyarakat Ogan Ilir - Otoman, Otoman; Panorama, Maya; Mikail, Kiki (Mahesa Research Center (PT. Mahesa Global Publishing), 2022)
This article examines the socio-cultural changes of society in the midst of the currents of globalization. Â It is assumed that there is a shift in the Besahian tradition in the Malay community of Embacang Ogan Ilir village which has been a social system in agricultural culture. This study aims to analyze the impact of such shifts because of the global influence of Islam and modernization in the agricultural system. The method used is qualitative explanatory with observation techniques, interviews, and documentation studies. The results showed that the Malay community of Embacang village is a community with a socio-cultural and religious background that is quite religious. The Besahian tradition as the culture of the Malay community of Embacang village reflects the values of religiosity influenced by Islam as a religion embraced by all citizens of its community, such as deliberation, help, togetherness, equality, justice, and friendship. The Besahian tradition on it has undergone an evolutive shift because of modernization in the agricultural system. Agricultural machinery technology is not only shifting the role of human labor, which is the fulcrum in the Besahian tradition, but also slowly but surely shifting the religiosity values contained in the tradition.